2018
DOI: 10.1186/s13033-018-0221-3
|View full text |Cite
|
Sign up to set email alerts
|

Building back better? Taking stock of the post-earthquake mental health and psychosocial response in Nepal

Abstract: BackgroundThe World Health Organization’s ‘building back better’ approach advocates capitalizing on the resources and political will elicited by disasters to strengthen national mental health systems. This study explores the contributions of the response to the 2015 earthquake in Nepal to sustainable mental health system reform.MethodsWe systematically reviewed grey literature on the mental health and psychosocial response to the earthquake obtained through online information-sharing platforms and response coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…A recent study after the 2015 earthquake on post-earthquake MHPSS responses in Nepal suggested that the activities had extraordinarily improved the process of building mental health system in Nepal. 24 The funding for mental health from the government and NGOs increased remarkably after the earthquake which was almost non-existent previously. The MOHP, with the support from the WHO and other NGOs, helped in establishing a coordinated response and reporting systems for MHPSS.…”
Section: Lessons From a Post-earthquake Nepalmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study after the 2015 earthquake on post-earthquake MHPSS responses in Nepal suggested that the activities had extraordinarily improved the process of building mental health system in Nepal. 24 The funding for mental health from the government and NGOs increased remarkably after the earthquake which was almost non-existent previously. The MOHP, with the support from the WHO and other NGOs, helped in establishing a coordinated response and reporting systems for MHPSS.…”
Section: Lessons From a Post-earthquake Nepalmentioning
confidence: 99%
“…MHPSS was included in the comprehensive disaster response teams at all 14 severely affected districts in Nepal during the recovery period. 24 Immediately after the earthquake, the government had declared a state emergency and called for international and national support which helped in increasing the global attention as well as in resources to provide immediate MHPSS. The immediate disaster response after the earthquake followed the IASC guideline on cluster approach and included different areas such as basic support for nutrition, health, water and sanitation, and shelter, etc.…”
Section: Lessons From a Post-earthquake Nepalmentioning
confidence: 99%
See 3 more Smart Citations